The complete mitochondrial genome sequence of Ptyas mucosus - Zhou, Bo (Mitochondrial DNA B Resour, 2016)
The complete mitochondrial genome sequence of the Ptyas mucosus was sequenced and reported for the first time using muscle tissue. The total length is 17 151 bp and sequence analysis showed its structure is in accordance with other snakes. The complete mitochondrial genome contains 2 rRNA genes, 21 tRNA genes, 13 protein-coding genes (PCGs), 2 control regions and 1 putative origin of L-strand replication. The gene order and nucleotide composition of P. mucosus are very similar with E. bimaculata, E. anomala and E. schrenckii. A phylogenetic tree of mitochondrial genomes indicated P. mucosus had the most closely relationship with E. bimaculata, and formed a monophyletic group with E. bimaculata, E. anomala and E. schrenckii.